2020
DOI: 10.3390/microorganisms8010138
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of ESBL-Producing Enterobacteria from Fruit Bats in an Unprotected Area of Makokou, Gabon

Abstract: In Gabon, terrestrial mammals of protected areas have been identified as a possible source of antibiotic-resistant bacteria. Some studies on antibiotic resistance in bats have already been carried out. The main goal of our study was to detect extended-spectrum beta-lactamases (ESBLs) that are produced by enterobacteria from bats in the Makokou region in Gabon. Sixty-eight fecal samples were obtained from 68 bats caught in the forests located 1 km from the little town of Makokou. After culture and isolation, 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 70 publications
3
23
0
Order By: Relevance
“…Strains belonging to this sequence types are recognized as a major contributor to the spread of carbapenemases and have been frequently associated with hospital outbreaks. In Gabon, phylogenetic analysis of bat guano isolates revealed that they were clustered with previously described human bacterial strains from Turkey and Tunisia, but without information on their relatedness to clonal groups (Mbehang Nguema et al 2020 ). All these and other studies suggest that antibiotic resistance in bat microbiome may vary locally and could be influenced by contact with wastes of antibiotic treatments of animals and humans (Swift et al 2019 ).…”
Section: Bat (Guano) Bacteriomementioning
confidence: 94%
See 1 more Smart Citation
“…Strains belonging to this sequence types are recognized as a major contributor to the spread of carbapenemases and have been frequently associated with hospital outbreaks. In Gabon, phylogenetic analysis of bat guano isolates revealed that they were clustered with previously described human bacterial strains from Turkey and Tunisia, but without information on their relatedness to clonal groups (Mbehang Nguema et al 2020 ). All these and other studies suggest that antibiotic resistance in bat microbiome may vary locally and could be influenced by contact with wastes of antibiotic treatments of animals and humans (Swift et al 2019 ).…”
Section: Bat (Guano) Bacteriomementioning
confidence: 94%
“…Recent studies have detected presence of extended spectrum β -lactamases (ESBLs) in Enterobacteriaceae isolates from bat guano. Mbehang Nguema et al ( 2020 ) reported for the first time the presence of multi-resistant ESBL-producing Enterobacteriaceae in fruit bats in Makokou. Their strains showed higher resistance to tetracycline, ciprofloxacin, and ofloxacin compared with the studies carried out in Nigeria (Oluduro 2012 ; Ajayi et al 2020 ).…”
Section: Bat (Guano) Bacteriomementioning
confidence: 99%
“…These include beta-lactams, macrolides, fluoroquinolones, tetracycline, and aminoglycosides. These superbugs are regarded as good markers to assess the dynamics of bacterial transfer between humans and wildlife, as resistant strains are thought to be naturally selected in anthropogenic environments and then transferred to wildlife [ 101 , 102 ]. A study in national parks in Gabon found E. coli strains resistant to amoxicillin and other antibiotics in the faecal material of western lowland gorillas ( G. gorilla gorilla ).…”
Section: Example 2: Escherichia Colimentioning
confidence: 99%
“…The authors wish to make the following corrections to this paper [ 1 ]: the prevalences of the ESBLs genes in the abstract were not the same as those reported in the results, and as such, the authors would like to replace the original abstract.…”
Section: Change In Abstractmentioning
confidence: 99%